Pemetaan Penelitian Rasio Financial Value Added (FVA) pada Perbankan Syariah dan Konvensional: Studi Bibliometrik VOSviewer dan Literature Review - Budianto, Eka Wahyu Hestya; Dewi, Nindi Dwi Tetria (LPPM STIEM BONGAYA, 2023)
This study aims to determine the research mapping regarding the Financial Value Added (FVA) ratio in Islamic and Conventional Banking using a mix-method approach, namely the VOSviewer bibliometric study and literature review. Data analysis techniques include: (1) mapping the distribution of journal publications around the FVA ratio; (2) mapping the results of the VOSviewer bibliometric visualization around the FVA ratio based on the number of clusters and their items; and (3) mapping research topics around the FVA ratio using a literature review study. The results showed that: (1) based on the distribution of journal publications, there were 25 journal publications regarding the FVA ratio; (2) based on the mapping of the VOSviewer bibliometric study, the network visualization results around the FVA ratio are divided into 4 clusters and 82 topic items; (3) based on the mapping of literature review studies, there are 2 topics around the influence of the FVA ratio and 2 topics about the determinants of the FVA ratio. The implications and contributions of this research are to map research topics around FVA ratios in Islamic and Conventional Banking which are often or rarely researched by researchers so that they can be a reference for subsequent researchers.